Financial Ratio and Return on Asset in Mining Companies: Mediating Effect of Firm Size - M Rizi; Anggraeni Yunita; Sumiyati Sumiyati; Julia Saputra (Master of Accounting Universitas Trunojoyo Madura, 2023)
This research aims to examine the effect of current ratio, debt to equity ratio and total asset turnover on return on assets with firm size as an intervening variable. The population of this study are mining companies listed on the Indonesia Stock Exchange in 2019-2021. The number of observations in this study was 66. The data analysis technique uses path analysis. This study found that current ratio and total asset turnover have a significant positive effect on return on assets, while the debt to equity ratio variable has no effect on return on assets. This study also found that firm size is able to mediate the relationship between debt to equity ratio and return on assets, but is unable to mediate the relationship between current ratio and total asset turnover on return on assets. This finding has implications for a consequence, namely that company size is one of the considerations in managing the rate of return on investment on company assets.